2001
DOI: 10.1103/physreve.64.061907
|View full text |Cite
|
Sign up to set email alerts
|

Indications of nonlinear deterministic and finite-dimensional structures in time series of brain electrical activity: Dependence on recording region and brain state

Abstract: We compare dynamical properties of brain electrical activity from different recording regions and from different physiological and pathological brain states. Using the nonlinear prediction error and an estimate of an effective correlation dimension in combination with the method of iterative amplitude adjusted surrogate data, we analyze sets of electroencephalographic (EEG) time series: surface EEG recordings from healthy volunteers with eyes closed and eyes open, and intracranial EEG recordings from epilepsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
1,344
1
45

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,454 publications
(1,410 citation statements)
references
References 49 publications
20
1,344
1
45
Order By: Relevance
“…Non-linearity in the brain is introduced even at the neuronal level [5], since the dynamical behaviour of individual neurons is governed by threshold and saturation phenomena. Given the highly non-linear nature of the neuronal interactions at multiple levels of temporal and spatial scales, the EEG appears to be an appropriate area for non-linear time series analysis [26].…”
Section: Introductionmentioning
confidence: 99%
“…Non-linearity in the brain is introduced even at the neuronal level [5], since the dynamical behaviour of individual neurons is governed by threshold and saturation phenomena. Given the highly non-linear nature of the neuronal interactions at multiple levels of temporal and spatial scales, the EEG appears to be an appropriate area for non-linear time series analysis [26].…”
Section: Introductionmentioning
confidence: 99%
“…the brain (Andrzejak et al, 2001). Many studies are known in which non-linear time series analysis techniques were applied to different kinds of EEGs from humans, such as recordings from healthy volunteers at rest , sleep (Babloyantz et al, 1985), during periods of cognitive activity (Theiler and Rapp, 1996), or from patients with acute ischemic stroke (Hwa and Ferree, 2002) or with diseases like Alzheimer's (Stam et al, 1995;Jelles et al, 1999), Parkinson's (Pezard et al, 2001), Creutzfeldt-Jakob (Babloyantz and Destexhe, 1988), epilepsy (Hornero et al, 1999), depression (Nandrino et al, 1994) and schizophrenia (Fell et al, 1995) in comparison with control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Several physiological signals, including cardiovascular and brain activity recordings, exhibit a partially non-linear behaviour (Andrzejak et al 2001, Hoyer et al 2002, Palacios et al 2007. Additionally, some authors have suggested that healthy systems have non-linear complex relationships that fail with ageing and disease (Costa et al 2005, Goldberger et al 2002.…”
Section: Introductionmentioning
confidence: 99%